The squareroot of x can also be expressed as x to the power of 1/2.
f(x) = squareroot x
f(x) = x ^ (1/2)
Now, take the usual approach to differentiating a function of x:
df(x)/dx = 1/2 * x ^ (1/2 - 1)
df(x)/dx = 1/2 * x ^ (-1/2)
X to a negative power is the same as 1/(x to the positive power).
df(x)/dx = 1/2 * 1 / (x ^ (1/2))
Replacing x^(1/2) with squareroot x again, you get:
df(x)/dx = 1/(2*squarerootx)
2007-01-12 10:35:01
·
answer #1
·
answered by Iago 2
·
0⤊
0⤋
All of the first six answers are correct, except that puggy (who is usually spot on!) let a minus sign creep in that shouldn't be there.
Were you asked to differentiate it from first principles?
If so, the easiest way is to use the definition
f'(x) = limit((f(x) - f(c))/(x - c) as c approaches x. [OK, purists, I know it's usually the other way round, but this way is valid too!]
Now (sqrtx - sqrtc)/(x - c), if we multiply both top and bottom by sqrtx + sqrtc , becomes
(x - c)/(x - c)(sqrtx + sqrtc) using the process that's usually for rationalising the denominator, but in this case it rationalises the numerator, which then cancels with the x - c in the denominator, leaving us with
1/(sqrtx + sqrtc)
As c approaches x, this approaches
1/(sqrtx + sqrtx)
= 1/(2*sqrtx).
Same as by the index method!!! Wonderful.
2007-01-12 19:09:23
·
answer #2
·
answered by Hy 7
·
0⤊
0⤋
Write it in exponent form, and use the rule of exponents for differentiating f(x)=x^n kinds of functions.
f(x)= x^(1/2)
f'(x)= (1/2) x ^(-1/2)
Done!
2007-01-12 18:33:30
·
answer #3
·
answered by Jerry P 6
·
0⤊
0⤋
Write square root of x as a power of x.
Then use the usual rule: multiply by the power, then reduce the power by 1.
2007-01-12 18:32:44
·
answer #4
·
answered by Gnomon 6
·
0⤊
0⤋
sqrt(x) can be expressed as x^(1/2), so you just use the power rule as normal.
f(x) = sqrt(x)
f(x) = x^(1/2)
f'(x) = (1/2)x^(-1/2)
We normally don't want negative exponents; taht's why we have to make x^(-1/2) into a fraction so we'll have a positive exponent.
f'(x) = (1/2) (-1/[x^(1/2)])
Merging into one fraction, we have
f'(x) = -1/[2x^(1/2)]
2007-01-12 18:33:20
·
answer #5
·
answered by Puggy 7
·
0⤊
0⤋
f(x)= x^(1/2)
I forget how to differentiate would it be
f'(x)=(1/2)x^(-1/2) ?
(hey it was 25 years ago)
2007-01-12 18:35:59
·
answer #6
·
answered by J C 5
·
0⤊
0⤋
(I hope I remember this right...)
That's the same as saying:
f(x) = x^(1/2)
So, the derivative is (1/2)x^(-1/2)
2007-01-12 18:32:22
·
answer #7
·
answered by Mathematica 7
·
0⤊
0⤋
sqrt(x) or x^(1/2)
f(x) = x^(1/2)
f'(x) = nx^(n - 1)
f'(x) = (1/2)x^((1/2) - 1)
f'(x) = (1/2)x^(-1/2)
ANS :
f'(x) = 1/(2x^(1/2))
f'(x) = 1/(2sqrt(x))
f'(x) = 1/(sqrt(4x))
Multiply top and bottom by sqrt(4x)
f'(x) = (sqrt(4x))/(4x)
f'(x) = (2sqrt(x))/(4x)
f'(x) = sqrt(x)/(2x)
ANS : f'(x) = sqrt(x)/(2x)
2007-01-12 23:58:06
·
answer #8
·
answered by Sherman81 6
·
0⤊
0⤋